(3eNJUQ UMjM eSdes - (3GdbQWHis; (3eSde Hf GdMLGL Hf eSde GdbTjQj GdfjSGHhQqi, CHh GdMSjf,J (B261 (3g` s
(3ChdgG (B:s
(3jHOC HcJGH GdEjeGf s
(3BNQgG (B:s
(3bGdJ dgG aHCi TF ZaQ dc abGdJ HcdeGJ cfJ Cbhdgf ai QbYJi bGdJ aEfJgjJ aOYhJ GdQbYI aEPG HgG ecJhH dG Edg EdGGddg CQVi HgG QHi hdG Edg EdG Gddg Cafi HgG YeQi hdG Edg EdG Gddg CdbG HgG QHi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B221 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B232s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B557s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs